Kidney transcriptome response to salinity adaptation in Labeo rohita - Harshini, Vemula; Shukla, Nitin; Raval, Ishan; Kumar, Sujit; Shrivastava, Vivek; Patel, Amrutlal K.; Joshi, Chaitanya G. (Frontiers in Physiology, 2022)
The increasing salinization of freshwater resources, owing to global warming, has caused concern to freshwater aquaculturists. In this regard, the present study is aimed at economically important freshwater fish, L. rohita (rohu) adapting to varying degrees of salinity concentrations. The RNA-seq analysis of kidney tissue samples of L. rohita maintained at 2, 4, 6, and 8 ppt salinity was performed, and differentially expressed genes involved in various pathways were studied. A total of 755, 834, 738, and 716 transcripts were downregulated and 660, 926, 576, and 908 transcripts were up-regulated in 2, 4, 6, and 8 ppt salinity treatment groups, respectively, with reference to the control. Gene ontology enrichment analysis categorized the differentially expressed genes into 69, 154, 92, and 157 numbers of biological processes with the p value < 0.05 for 2, 4, 6, and 8 ppt salinity groups, respectively, based on gene functions. The present study found 26 differentially expressed solute carrier family genes involved in ion transportation and glucose transportation which play a significant role in osmoregulation. In addition, the upregulation of inositol-3-phosphate synthase 1A (INO1) enzyme indicated the role of osmolytes in salinity acclimatization of L. rohita. Apart from this, the study has also found a significant number of genes involved in the pathways related to salinity adaptation including energy metabolism, calcium ion regulation, immune response, structural reorganization, and apoptosis. The kidney transcriptome analysis elucidates a step forward in understanding the osmoregulatory process in L. rohita and their adaptation to salinity changes.